(untitled) (Journal of Philosophy Culture and Political Science, 2019)
The article considers the issue of the essence of Islamic identity and its significance in the historical and cultural tradition. In Kazakhstan, as in many other Central Asian regions, whose population is predominantly Muslim, Islam was formed in the context of an organic connection with local national and cultural traditions, among which the influence of Turkic cultural traditions can be noted. The authors analyzed the main aspects of Islamic identity and its formation in the sociocultural, geopolitical experience of the national culture of both the Islamic world and the European space. The modern global world leads to the unification of cultural, political and religious processes. In such circumstances, the destruction processes of identification of society and the individual are occurs. The loss of own cultural / religious identity has become one of the main problems in modern society. National culture is formed in the process of history and the logic of traditional relations. The article substantiates that the Kazakh Islamic identity was formed in the national culture, incorporating customs and traditions that did not contradict the Islamic system of values, and the traditions of spirituality were synthesized in the Islamic paradigm. The preservation of Islamic identity is directly related to the problem of national cultural identity and, in general, with the problem of preserving cultural heritage. Key words: Culture, National culture, Religious identity, Islamic identity, Tradition.